2017
DOI: 10.1590/1806-9282.63.01.78
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and metalloproteinases 2 and 9: What is their relation with breast cancer?

Abstract: Zinc is the catalytic component of proteins that regulate responses to DNA damage, intracellular signaling enzymes, and matrix metalloproteinases, which are important proteins in carcinogenesis. The objective of this review is to bring current information on the participation of zinc and matrix metalloproteinases types 2 and 9 in mechanisms involved in the pathogenesis of breast cancer. We conducted a literature review, in consultation with the PubMed, Lilacs, and Scielo databases. The zinc and cysteine residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…Hrabec et al have reported that the levels of plasma and serum MMP-9 in patients with lung cancer are significantly higher than those in the control group (Hrabec et al, 2001). High levels of MMP-9 have been found in blood samples from patients with breast, colorectal and gastric cancers, and melanoma (Kostova et al, 2012;Holanda et al, 2017;Nikkola et al, 2005;Mroczko et al, 2009 In our study cancer patients had significantly higher MMP-9 levels compared to control patients, regardless of tumor stage. It is possible that this factor might be involved and dominate in early tumor progression stages.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Hrabec et al have reported that the levels of plasma and serum MMP-9 in patients with lung cancer are significantly higher than those in the control group (Hrabec et al, 2001). High levels of MMP-9 have been found in blood samples from patients with breast, colorectal and gastric cancers, and melanoma (Kostova et al, 2012;Holanda et al, 2017;Nikkola et al, 2005;Mroczko et al, 2009 In our study cancer patients had significantly higher MMP-9 levels compared to control patients, regardless of tumor stage. It is possible that this factor might be involved and dominate in early tumor progression stages.…”
Section: Discussionsupporting
confidence: 53%
“…Several studies have assessed the predictive value of MMP-2 but have arrived at opposite results. Several authors have reported the increase of plasma/serum levels of MMP-2 in patients with colorectal cancer, melanoma, and breast and gastric cancers (Kostova et al , 2012;Holanda et al, 2017;Roopali et al, 2009). On the other hand, Kuvaja et al reported that low serum levels of circulating MMP-2 and TIMP-2 are associated with a poor prognosis in bladder cancer patients (Kuvaja et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These events include the activity of MMPs and their tissue inhibitors (TIMPs) which seem to be involved in the propagation of various tumors, including breast cancer (3,15). The expression of MMPs is generally very low and mainly regulated by transcription.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are main regulators during several phases of the angiogenic process, from deposition and remodeling of ECM components to cell proliferation and migration (2). They contribute to angiogenesis either by degrading basement membranes or by promoting and maintaining the angiogenic phenotype (1,3). In breast cancer progression, particular importance was given to MMP-2 and MMP-9 due to their specificity for Collagen IV and possible implication in metastatic spread (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…(5) Trace elements have been implicated in the pathogenesis of breast cancer. (6) According to Holanda et al (7) increases in zinc concentration in the cellular compartment and reduction of this trace element in the blood of patients with breast cancer appear to alter the activity of metalloproteinases 2 and 9 that contribute to the occurrence of malignancy. However, new studies that determine the effectiveness of these inhibitors in breast carcinoma are still needed.…”
Section: Introductionmentioning
confidence: 99%